Expression of LLT1 and its receptor CD161 in lung cancer is associated with better clinical outcome. (4th May 2018) - Braud, Véronique M.; Biton, Jérôme; Becht, Etienne; Knockaert, Samantha; Mansuet-Lupo, Audrey; Cosson, Estelle; Damotte, Diane; Alifano, Marco; Validire, Pierre; Anjuère, Fabienne; Cremer, Isabelle; Girard, Nicolas; et al.
ABSTRACT: Co-stimulatory and inhibitory receptors expressed by immune cells in the tumor microenvironment modulate the immune response and cancer progression. Their expression and regulation are still not fully characterized and a better understanding of these mechanisms is needed to improve current immunotherapies. Our previous work has identified a novel ligand/receptor pair, LLT1/CD161, that modulates immune responses. Here, we extensively characterize its expression in non-small cell lung cancer (NSCLC). We show that LLT1 expression is restricted to germinal center (GC) B cells within tertiary lymphoid structures (TLS), representing a new hallmark of the presence of active TLS in the tumor microenvironment. CD161-expressing immune cells are found at the vicinity of these structures, with a global enrichment of NSCLC tumors in CD161 + CD4 + and CD8 + T cells as compared to normal distant lung and peripheral blood. CD161 + CD4 + T cells are more activated and produce Th1-cytokines at a higher frequency than their matched CD161-negative counterparts. Interestingly, CD161 + CD4 + T cells highly express OX40 co-stimulatory receptor, less frequently 4-1BB, and display an activated but not completely exhausted PD-1-positive Tim-3-negative phenotype. Finally, a meta-analysis revealed a positive association of CLEC2D (coding for LLT1) and KLRB1 (coding for CD161) gene expression with favorable outcome in NSCLC, independently of the size of T and B cell infiltrates. These data are consistent with a positive impact of LLT1/CD161 on NSCLC patient survival, and make CD161-expressing CD4 + T cells ideal candidates for efficient anti-tumor recall responses.